Dengue Vaccination: A Practical Guide for Clinicians - Kay Choong See (Vaccines)
Dengue is a growing global public health challenge, with rising incidence and case fatality rates fueled by urbanization and climate change. The substantial mortality, morbidity, and economic burden associated with the disease underscore the need for effective prevention strategies, including vector control, personal protective measures, and vaccination. This narrative review provides a practical guide for clinicians to ensure the appropriate administration of dengue vaccines to at-risk groups, such as individuals in endemic regions and travelers to these areas. Live-attenuated tetravalent dengue vaccines, including Dengvaxia®, Qdenga®, and Butantan-DV, have demonstrated efficacy in clinical trials but require careful use due to the risk of antibody-dependent enhancement (ADE). To mitigate this risk, guidelines recommend vaccination primarily for individuals with prior confirmed dengue infection, emphasizing the importance of accessible and affordable point-of-care rapid testing. Co-administration of dengue vaccines with other live-attenuated or inactivated vaccines has been shown to be safe and immunogenic, broadening their potential application. However, live-attenuated vaccines are contraindicated for immunocompromised individuals and pregnant women. Enhancing clinician awareness, expanding diagnostic capabilities, and prioritizing high-risk populations are critical steps to optimize vaccination strategies. Combined with robust prevention programs, these efforts are essential to reducing the global burden of dengue and mitigating its impact.